An experimental study of new rule javelins - Chowdhury, H.; Alam, F.; Muscara, A.; Mustary, I. (Procedia Engineering, 2013)
This paper presents a comparative study of three new rule javelins (800 g) used in elite competitions. Wind tunnel experiments were conducted on three commercially manufactured javelins (Hart Sports, Nordic Master 60 and Nordic Airglider) to investigate their aerodynamic characteristics. The aerodynamic drag, lift and pitching moment were measured over a range of wind speeds (25 to 33 m/s) for a range of angles of attack from 0 to 35 degree relative to the wind direction. The results suggest that the optimal release angles for each of the javelins are different due to their physical design. The angles of attack for highest lift-to-drag ratio for Hart Sports, Nordic Master 60 and Nordic Airglider javelins were found at 15°, 25° and 30° respectively. The findings of this study also indicate that Airglider javelin has better pitching moment stability than other two javelins.